Prognostic information of gastric carcinoma using Goseki system in relation to nuclear organizer region (AgNOR) and proliferating cell nuclear antigen (PCNA) expression (Bangladesh Journal of Medical Science, 2010)
Objective: The present study was undertaken to find out the relationship of Goseki grading system (I-IV) with existing classification of WHO, Lauren and tumour differentiation of gastric carcinoma and its prognostic information in relation to AgNOR & PCNA expression. Materials and methods: To assess the reproducibility and usefulness of Goseki grading system thirty five gastric carcinoma were selected from January 2007 to July 2009 in the department of Pathology, Burdwan Medical College in West Bengal, India and analyzed in relation to existing grading system by chi-squared testing. Mean AgNOR count & mean PCNA leveling index quantities of different tissue sections were assessed according to different classification system of gastric carcinoma and interobserver variations of all data were evaluated from Spearman Rank-order Correlation Coefficient (rs ). Results: Highly significant predictable correlation of Goseki grading system for existing classification of gastric carcinoma was obtained statistically. Increasing values of mean AgNOR count and PCNA leveling index (2.35% & 15.14%, 2.91% & 21.32%, 3.08 %& 24.76% and 3.2% & 25.12 respectively) were observed from Grade I – IV of Goseki grade. Mucin rich (3.05% & 23.22%) and tubule poor (3.14% & 24.76%) tumours higher values than mucin poor (2.71% & 19.95%) and tubule rich (2.63% & 18.23%) tumors. No significant correlations were observed in other grading system. Conclusion: Following Goseki grading system increasing expression of proliferating marker in mucin rich than mucin poor tumours and tubules poor than tubules rich tumors indicate poor prognosis and tumour behavior. Simple system may help to select patients for adjuvant therapy. Key words: Goseki grade; gastric carcinoma; AgNOR; PCNA. DOI: 10.3329/bjms.v9i2.5655Bangladesh Journal of Medical Science Vol.09 No.2 Apr 2010 pp.76-86